The value of x such that f(x) = g(x) is x = 3
<h3>Quadratic equation</h3>
Given the following expressions as shown
f(x) = x^3-3x^2+2 and;
g(x) = x^2 -6x+11
Equate the expressions
x^3-3x^2+2 = x^2 -6x+11
Equate to zero
x^3-3x^2-x^2+2-11 = 0
x^3-3x^2-x^2 + 6x - 9 = 0
x^3-4x^2+6x-9 = 0
Factorize
On factorizing the value of x = 3
Hence the value of x such that f(x) = g(x) is x = 3
Learn more on polynomial here: brainly.com/question/2833285
#SPJ1
You have to have more than one LCD or it won't work for one you have to have 2 or more fraction to complete this
Answer:
never
Step-by-step explanation:
Answer:
CHEESE
Step-by-step explanation:
SKDMALSD